PERBANDINGAN IMPLEMENTASI PROGRAM SMART CITY DI PULAU JAWA DAN SUMATERA: Comparison of the Implementation of Smart City Programs on the Islands of Java and Sumatra - Rai Nurauliana; Jumanah Jumanah; Saiful Fadillah; Sela Diana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Smart cities have spread all over the world and are becoming popular. The important dimensions of a smart city consist of a smart economy, smart mobility, smart environment, smart people, smart living, and smart governance. There are as many as 25 cities that are pioneers of smart cities in Indonesia. Smart city planning is a global agenda as a conceptual and practical response to various urban crises in an increasingly worrying world. The legal basis for implementing the smart city program has been regulated by law. The focus of development is on basic urban facilities and infrastructure. Smart cities take advantage of technology. The increasing flow of globalization requires various countries to compete. The government cooperates to harmonize the interests and goals of various sectors. A number of smart city programs have been implemented in various districts/cities on the islands of Java and Sumatra. Every city government competes to brand its city. bibliometric mapping using network visualization and Co-Word density. Smart City which supports efforts to increase development and management of cities based on information and communication technology as well as to support services in the health sector is one of the needs that must be met by the community.